Predicting Suicidal Thoughts Based on Components of difficulty in emotion regulation in suicide ideators - Seyed hamed Sadjadpour; Leila Heydarinasab; Mohammad Shairi; Mohammad Gholami fesharaki (طب انتظامی, 2020)
Aims: Suicide is a fundamental cause of premature deaths in the world. Therefore, it is very important to identify predictors of suicide. The aim of the present study was to predict suicidal ideation based on the components of difficulty in emotion regulation in suicide ideators. Materials & Methods: The statistical population of this study was the patients referring to the psychiatric clinics in Imam Reza and Imam Ali hospitals in Bojnourd with suicidal thoughts in the spring of 2019, which, according to the latest report, consisted of 233 people. Using the available sampling method, 141 patients were selected and completed the difficulty in emotion regulation questionnaire and Beck's suicidal ideation questionnaire. Findings: In the present study, data were analyzed based on the information from 141 subjects, 55 of whom were male, and 86 were female. The mean age of participants was 23.5 years. The results of regression analysis showed that, among the components of difficulty in emotion regulation, three subscales of limited access to emotion regulation strategies (P<0.001), non-acceptance of emotional responses (P<0.05), and lack of emotional clarity (P<0.01) have been able to predict the suicidal ideation score significantly. Conclusion: Based on the findings of this study, it can be concluded that emotion regulation strategies, acceptance of emotional responses, and emotional clarity can predict suicidal thoughts.